Biological pretreatment of lignocellulosic biomass as a sustainable option for biofuel production - Naveen Kumar; Himanshu Saini; Neeraj K. Aggarwal; Nishu Jangra; Kavita Dhiman; Ishu Sangwan (Next Sustainability, 2025)
Biofuels derived from lignocellulosic material are renewable, sustainable, and ecologically friendly, presenting a significant alternative to fossil fuels. However, before saccharification, pretreatment is an important stage in arranging the lignocellulose layers. The biological treatment of lignocellulose, utilizing microbes such as bacteria and fungi, is increasingly prevalent due to its financial and environmental benefits. Choosing the right microbial consortia with care is essential to effectively pretreating biomass. Our collection of exceptionally promising bacteria and/or fungi is capable of manufacturing a range of extracellular enzymes, such as lignases, cellulases, and hemicellulases. It can effectively treat lignocellulosic biomass biologically in order to produce biofuels. This review article offers an in-depth exploration of biological pretreatment strategies for lignocellulosic biomass, highlighting key mechanisms, innovative technologies, influencing factors, and the latest advancements shaping current research in the field.